2017
DOI: 10.1002/ccr3.920
|View full text |Cite
|
Sign up to set email alerts
|

Repeated successful use of eltrombopag in chronic primary immune thrombocytopenia: description of an intriguing case

Abstract: Key Clinical MessageThrombopoietin receptor agonists (TPO‐RAs) are used as effective alternative treatments in ITP patients unresponsive to first‐/second‐line therapies. TPO‐RAs can also be used to normalize platelet count to safely perform invasive procedures and chemotherapy, in case of malignancies. In few responsive patients, TPO‐RAs can be suspended maintaining a sustained response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…While it was previously thought that patients with ITP would have to remain on TPO-RAs indefinitely to maintain adequate platelet counts, recent case reports and cohort studies have shown that selected patients with ITP can safely discontinue treatment. [7][8][9][10][11][12][13][14][15][16][17][26][27][28][29][30][31][32][33][34][35][36][37][38][39] However, to date, no formal guidelines identify which patients can successfully discontinue TPO-RAs. 4,20 In response to this need, we developed consensus statements on when it is appropriate to consider tapering TPO-RAs; broad guidance on how to taper patients off therapy, how to monitor patients after discontinuation, and how to restart therapy in the event of relapse is also provided.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While it was previously thought that patients with ITP would have to remain on TPO-RAs indefinitely to maintain adequate platelet counts, recent case reports and cohort studies have shown that selected patients with ITP can safely discontinue treatment. [7][8][9][10][11][12][13][14][15][16][17][26][27][28][29][30][31][32][33][34][35][36][37][38][39] However, to date, no formal guidelines identify which patients can successfully discontinue TPO-RAs. 4,20 In response to this need, we developed consensus statements on when it is appropriate to consider tapering TPO-RAs; broad guidance on how to taper patients off therapy, how to monitor patients after discontinuation, and how to restart therapy in the event of relapse is also provided.…”
Section: Discussionmentioning
confidence: 99%
“…We used a validated methodology to develop the first set of consensus statements from US clinical experts on tapering TPO‐RA monotherapy in patients with persistent or chronic primary ITP. While it was previously thought that patients with ITP would have to remain on TPO‐RAs indefinitely to maintain adequate platelet counts, recent case reports and cohort studies have shown that selected patients with ITP can safely discontinue treatment 7‐17,26‐39 . However, to date, no formal guidelines identify which patients can successfully discontinue TPO‐RAs 4,20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two small prospective studies identified around 30% of patients who were able to completely discontinue eltrombopag for at least 12 weeks while maintaining hemostatic platelet counts [10,11]. These rates of therapy-free responses (TFRs) are in line with those reported in adult and pediatric patients treated with TPO-RA [12][13][14][15][16][17][18][19][20][21][22]. Although to date we still cannot identify on which patients this approach is likely to be most successful, a complete response to low doses of TPO-RA and a diagnosis of ITP < 1 year could lead to higher TFRs [15,23].…”
Section: Introductionmentioning
confidence: 59%